Too right-wing for police integrity? General socio-political attitudes connect work experiences to police integrity. (14th September 2022) - Van Droogenbroeck, Filip; Kutnjak Ivkovic, Sanja; Spruyt, Bram
ABSTRACT: Police integrity is a crucial steppingstone in police administrators' long-term goals of obtaining legitimacy and yielding citizens' evaluations of the police as a legitimate institution. This paper investigates the relationship between work-related experiences and police integrity, as well as the degree to which this relationship is mediated by well-known socio-political attitudes such as authoritarianism, ethnic prejudice, and social dominance orientation. Using structural equation modelling of the responses provided by 1, 255 members of the Belgium police, the work-related characteristics, socio-political attitudes, and organisational dimensions of police integrity are related to three outcomes of police integrity. Results show that police officers in the field and those who had more frequent contacts with victims and perpetrators of crimes evaluate misconduct to be less serious, are less willing to say that they would report the behaviour, and advocate less severe disciplinary sanctions. Generalised socio-political attitudes related to prejudice mediate work-related experiences and perceptions of peer police integrity and are in turn negatively related to police integrity outcomes. These findings illustrate that police officers do not operate in a social vacuum as these general socio-political attitudes are non-occupation specific. This suggests that police integrity training programmes not only need to target work-related characteristics, such as an open culture to discuss problems, but also need to target general socio-political attitudes to foster police integrity.